Chemical and microbiological responses of heavy metal contaminated sediment subject to washing using humic substances - Wen, Jia; Xing, Lang; Wang, Yongxu; Zeng, Guangming (Environmental science and pollution research international, 2019)
Washing of contaminated soils or sediments using humic substances (HS) extracted either from source-rich materials or compost has been tested effective to remove various heavy metals. Nevertheless, the remaining chemical fractionation of metals and post-washing biological responses were not discussed in previous research. In this study, we used a HS extracted from green waste compost to wash off Cd, As, and Ni from a contaminated sediment, and evaluated the washing effect on sediment microbes by measuring a series of indexes with regard to microbial biomass and enzyme activities. Results showed that HS washing was more effective in removing the cationic metals Cd and Ni than the anionic metal As. The highest HS dose of 2000 mg L −1 resulted in 24.5-, 33.1-, and 12-fold increases of removal for Cd, Ni, and As, respectively. The remaining Cd and As were found to migrate to less stable fractions, whereas the remaining Ni was dominantly found in the residual fraction. Increases of metal removal efficiency, microbial biomass, and dehydrogenase activity were found to correlate with the increase of HS concentrations. Increasing doses of HS slightly altered sediment pH to the lower range but did not cause any significant effect on microbial activities. The study proves that HS washing is indeed a more environmental-friendly strategy than many existing washing agents which have exerted various side effects on soil properties.